STRATEGI KONTEN KREATOR DALAM MENINGKATKAN CITRA POLRESTABES PALEMBANG MELALUI SOSIAL MEDIA - Vita Anarkiz; Dwi Maharani (Journal of Innovation Research and Knowledge, 2025)
As a National Security and Order Actor (KAMTIBNAS) it is important for the Police to have a positive image that can be trusted. This positive image can be built through effective and creative communication, including on social media which can be a form of publication of reports to the wider community regarding the programs that have been undertaken in helping the community. Therefore, this article explains how the Strategy of a Content Creator in improving the Image of the Palembang Police through Socialmedia based on experience during this Independent study process This research uses a qualitative method. The content creation process involves a long process in order to create content that is effective in improving the image of the Palembang Police